Cultures of Computer Game Concerns The Child Across Families, Law, Science and Industry (Edition 1) - Sörensen, Estrid (transcript Verlag, 2018)
The same computer games are played by youths all over the world, and worldwide games become matters of concern in relation to children: worries rise about addiction, violence, education, time, and economy. Yet, these concerns vary depending upon where they are situated: in families, legal contexts, industry or science. They also play out differently across countries and cultures. This situated nature of computer game concerns is generally neglected. Not in this book: It gives a detailed mosaic of the complex and multiple everyday realities of computer game concerns in relation to children, as they are variably situated throughout society and across cultures.